Acute and chronic glucocorticoid treatments regulate astrocyte-enriched mRNAs in multiple brain regions in vivo - Carter, Bradley S.; Hamilton, David E.; Thompson, Robert C. (Frontiers in Neuroscience, 2013)
Previous studies have primarily interpreted gene expression regulation by glucocorticoids in the brain in terms of impact on neurons; however, less is known about the corresponding impact of glucocorticoids on glia and specifically astrocytes in vivo. Recent microarray experiments have identified glucocorticoid-sensitive mRNAs in primary astrocyte cell culture, including a number of mRNAs that have reported astrocyte-enriched expression patterns relative to other brain cell types. Here, we have tested whether elevations of glucocorticoids regulate a subset of these mRNAs in vivo following acute and chronic corticosterone exposure in adult mice. Acute corticosterone exposure was achieved by a single injection of 10 mg/kg corticosterone, and tissue samples were harvested two hours post-injection. Chronic corticosterone exposure was achieved by administering 10 mg/mL corticosterone via drinking water for two weeks. Gene expression was then assessed in two brain regions associated with glucocorticoid action (prefrontal cortex and hippocampus) by qPCR and by in situ hybridization. The majority of measured mRNAs regulated by glucocorticoids in astrocytes in vitro were similarly regulated by acute and/or chronic glucocorticoid exposure in vivo. In addition, the expression levels for mRNAs regulated in at least one corticosterone exposure condition (acute/chronic) demonstrated moderate positive correlation between the two conditions by brain region. In situ hybridization analyses suggest that select mRNAs are regulated by chronic corticosterone exposure specifically in astroctyes based on (1) similar general expression patterns between corticosterone-treated and vehicle-treated animals and (2) similar expression patterns to the pan-astrocyte marker Aldh1l1. Our findings demonstrate that glucocorticoids regulate astrocyte-enriched mRNAs in vivo and suggest that glucocorticoids regulate gene expression in the brain in a cell type-dependent fashion.